In Deep Relation with Creation: Letting Eco-Theology Speak from Sámi Indigenous Religious Practices - Matthaei, Lea Kirsten (Studia theologica, 2025)
The present article lets eco-theology speak from two Sámi indigenous religious practices, sivdnidit “blessing”, and jearrat lobi “asking for permission”. The Sámi are the indigenous people of Sápmi, a region covering the northern parts of Norway, Sweden, Finland and Russia. Sámi indigenous religion has often only been accepted as folk belief, practice or lived religion, but not theology. This article, however, discusses the voice of Sámi eco-theology within Sámi indigenous religious practices. Sámi indigenous religion, cosmology, ontology and theology challenge our understanding of solutions for the climate crisis, the so-called green shift, and call for ethical practice. Central to Sámi eco-theology as grounded in the practices of blessing and asking for permission are the principles of relationality, humility, interdependence, and interconnectedness, which embody integral ecology. The article illustrates the relevance and timeliness of letting eco-theology speak from Sámi indigenous practices by considering an example of land disputes with regards to the green energy transition in Norway. While such disputes are usually considered through a legal or political lens, the article explores new perspectives by considering the underlying cosmological beliefs and understandings of reality.